Successful colonoscopic decompression of colocolic intussusception with polypectomy in a five-year-old - Omar El-Ghazzawy; Ellen M. Encisco; Reinaldo Garcia-Naveiro; Justin T. Huntington (Elsevier, 2022)
The incidence of colocolic intussusception is rare in the pediatric population. When it is encountered, there should be a high index of suspicion for colonic neoplasm acting as the lead point. Our case involves a 5-year-old male who presented with left-sided colocolic intussusception secondary to multiple colonic polyps. He underwent colonoscopy with successful reduction of the intussusception in addition to endoscopic removal of multiple colonic polyps. The use of endoscopy to resolve the intussusception proved to be a valuable tool for our patient as it avoided subjecting the patient to an operation and allowed for surveillance of the remainder of the colon. Level of evidence: IV.